An analysis of the proposed Indian data protection act - Oberoi, Sundeep (IIPA Digest: Building capacity for governance)
Introduction In a landmark judgment delivered on the 24th of August 2017, now popularly known as the Puttaswamy judgement, a 9 judge bench unanimously ruled that every citizen of India had a fundamental right to privacy which was guaranteed by the Constitution of India within Article 21 in particular and Part III on the whole. In response to the need to protect the personal data of citizens, The Union Government of India, acting through the Ministry of Electronics and Information Technology constituted a Committee of Experts to deliberate on a data protection framework for India. Justice B N Srikrishna was appointed as the Chairman and the commi. Reproduced
Keywords: Indian data protection act